Ecological implications of organic carbon dynamics in the traps of aquatic carnivorous Utricularia plants - Sirov, Dagmara; Borovec, Jakub; Picek, Tom X; Adamec, Lubom R; Nedbalov, Linda; Vrba, Jaroslav (Functional plant biology, 2011)
Rootless aquatic carnivorous Utricularia exude up to 25% of their photosynthates into the trap lumen, which also harbours a complex microbial community thought to play a role in enhancing Utricularia nutrient acquisition. We investigated the composition of organic carbon in the trap fluid, its availability for microbial uptake, the influence of plant nutrient status and trap age on its biodegradability, and the composition of prokaryotic assemblages within the traps of three aquatic Utricularia species. Using ion chromatography and basal respiration rate measurements we confirmed that up to 30% of total dissolved organic carbon in Utricularia trap fluid in oligotrophic conditions was easily biodegradable compounds commonly found in plant root exudates (mainly glucose, fructose and lactate). The proportion of these compounds and their microbial utilisation decreased with increasing mineral nutrient supply and trap age. Fluorescence in situ hybridisation analyses showed that microbial trap assemblages are dominated by alpha and beta Proteobacteria, and that the assemblage composition is affected by changes in the ambient mineral nutrient supply. We suggest that organic carbon dynamics within the traps, involving both the plant and associated microbial assemblages, underlies the acquisition of key nutrients by Utricularia and may help explain the evolutionary success of the genus.